Analisis Pendapatan Peternak Sapi Potong Sistem Pemeliharaan Intensif dan Konvensional di Kabupaten Sleman Yogyakarta - . Sundari (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2009)
The study was purposed to find out income and feasibility of beef cattle farmers by intensive and conventional systems. This evaluation was done May  – July 2005. The matter used in this evaluation was 70  beef cattle farmers in Sleman Regency, using survey method. The result showed that beef cattle farmer profit by intensive system was Rp 36,943,964/year or Rp 3,078,663.7/month while by conventional system Rp 3,732,135.56 /year or Rp 311,011.3/ month. Rentability of beef cattle farmer by intensive system 46,3 % and conventional system 29,9 %. The conclusion indicated that beef cattle farmer both system by intensive and conventional were feasible. Key words:  Income, beef cattle farmer, intensive, conventional system